1996
DOI: 10.1111/j.1530-0277.1996.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Chronic Ethanol Consumption on Hepatic Mitochondrial and Cytoplasmic Ribosomes

Abstract: The effects of chronic ethanol consumption on the properties of mitochondrial and cytoplasmic ribosomes were investigated in rat liver. Sedimentation properties of purified mitochondrial (55S) and cytoplasmic (80S) ribosomes were determined by analyses on sucrose density gradients. Mitochondrial ribosomes from control animals moved further in the gradients than did those isolated from ethanol-fed rats, which suggests that ethanol ribosomes have a lower molecular weight. In addition, mitochondrial from ethanol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Mitochondrial energization was determined as the retention of the dye 3,3Ј-dihexyloxacarbocyanine (DiOC 6 [3]) (Molecular Probes Inc., Eugene, OR). Cells were loaded with 100 nmol/L of DiOC 6 (3) during the last 30 minutes of treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial energization was determined as the retention of the dye 3,3Ј-dihexyloxacarbocyanine (DiOC 6 [3]) (Molecular Probes Inc., Eugene, OR). Cells were loaded with 100 nmol/L of DiOC 6 (3) during the last 30 minutes of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…One of the primary sites manifesting damage brought on by ethanol is the mitochondria. [3][4][5][6] Mitochondria isolated from ethanolfed rats are known to be deficient in respiratory-chain components and ATP production during periods of stress, and they show damage to mitochondrial DNA. 7,8 Such effects of ethanol on mitochondrial function may result in lipid peroxidation and impairment of ATP production during exposure to stresses such as hypoxia or inflammatory cytokines, leading to further injury of the mitochondria and cell.…”
mentioning
confidence: 99%
“…In addition, mitoribosomes isolated from ethanol-fed animals exhibit significant decreases in their translational diffusion coefficients (1.02 × 10 -7 cm 2 s -1 , ethanolfed; 1.10, control) (6), and larger hydrodynamic diameters (42.1 nm, ethanol-fed; 39.1, control) (6). These ethanol-elicited alterations in the physicochemical properties of the hepatic mitoribosome are accompanied by significant amounts of disassociation of the intact 55S monosome (8-14%) into its constituent subunits (5,6). Further, in vitro studies on the translation capacity of mitoribosomes have revealed that while total translation activity is depressed by 29% in the ethanol-fed animals relative to the controls, no difference is detected between the two treatment groups in the activity of the intact monosomes (6), which suggests that the decrease in translation activity observed in ethanol-fed animals is caused by either increased disassociation or decreased association of functional ribosomes rather than impaired activity of intact monosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of potential molecular mechanisms may explain this decrease, one specific mechanism involves the impaired assembly of mitoribosomes. Investigations conducted by the Cunningham lab have revealed that mitoribosomes isolated from young male rats (200 g) fed ethanol (Lieber-DiCarli diet) (4) for 31 d exhibit decreased sedimentation rates through sucrose density gradients when compared with their paired controls (5,6). Further, sedimentation velocity experiments reveal a significant decrease in the average sedimentation coefficient for the intact ethanol mitoribosome (52.2, ethanol-fed; 53.7, control) (6) as well as for the small ribosomal subunit (27.0, ethanol-fed; 28.3, control) (6).…”
Section: Introductionmentioning
confidence: 99%
“…the global mitochondrial proteome, has only recently been investigated (4,5). Early studies by Cunningham and colleagues demonstrated that chronic alcohol consumption decreases the synthesis of the 13 mitochondrial encoded proteins that are components of complexes I, III, IV, and V (6,7) due to defects in mtDNA (4,8,9) and a decrease in functional mitochondrial ribosomes (10,11). It is important to note however that there are well over 600 proteins that comprise the mitochondrial proteome (12,13), and that close to 100 of these are components of the oxidative phosphorylation system, most of which are encoded by the nuclear genome.…”
Section: Introductionmentioning
confidence: 99%